TARI RENTAK BULEAN SUATU TRADISI PENGOBATAN SUKU TALANG MAMAK DI DESA TALANG JERINJING KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Hidayat, Rahmad; Saiman, Marwoto; ', Isjoni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:Bulean is a ceremony of traditional medicine that is led by a handler(Kumantan) assisted by pebayu and flunky Belian. During the ceremony drum (ketobang)have an important role to accompany the dance magic and incantations sung by thehandler in a state of unconsciousness. The ceremony consists of several stages: see thedisease, find a cure, create medicines, medicines and closes the medicine (memotimedicines) The purpose of this research is to find out the history of dance in unison Buleanin District Rengat West Indragiri Hulu in Riau, to know the process of implementation ofdance in unison Bulean in District Rengat West Indragiri Hulu in Riau, To determine thefunction of dance in unison Bulean in District Rengat West County Indragiri Hulu in Riauprovince.The method used in this research is the historical method and qualitative methods.Data were obtained from interviews and analyzed in its own language. The researchlocation is in Talang Jerinjing Rengat Western District of Indragiri Hulu. When the studystarted from the seminar proposal to the Final exam. Data collection techniques used wereobservation, interview techniques, technical documentation and technical literature.BuleanRentak dance comes from the word meaning unison footwork lope, while Bulean namecomes from wood that Wood Bulean. Bulean wood is the material for making ketobung.Ketobung a long drum that is specifically used as a dance accompanist Rentak Bulean. It'shard to know when and who created the dance Rentak Bulean for the first time so presentin the midst of community life Indragiri Hulu, it is because there is no clear data about thedances. Bulean Rentak this dance usually displayed in certain events and serves as a danceentertainment in society Indragiri Hulu.Keywords: Dance Rentak Bulean